2010
DOI: 10.2105/ajph.2009.188664
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-Related Health Risks Among Persons With HIV in the Strategies for Management of Antiretroviral Therapy Clinical Trial

Abstract: Objectives We sought to determine smoking-related hazard ratios (HRs) and population-attributable risk percentage (PAR%) for serious clinical events and death among HIV-positive persons, whose smoking prevalence is higher than in the general population. Methods For 5472 HIV-infected persons enrolled from 33 countries in the Strategies for Management of Antiretroviral Therapy clinical trial, we evaluated the relationship between baseline smoking status and development of AIDS-related or serious non-AIDS event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
190
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(206 citation statements)
references
References 47 publications
11
190
2
3
Order By: Relevance
“…28 Among HIV patients, quitting smoking also appears to convey substantial health benefits. For example, Lifson et al 26 reported that mortality among HIV patients in their sample was significantly higher throughout the follow-up period for current smokers than for former smokers. Current smokers were also more likely than former smokers to experience AIDS-related events (which include diseases meeting the revised CDC AIDS case definition as well as other conditions associated with HIV-related immunodeficiency, such as esophageal candidiasis), cardiovascular disease, non-AIDS cancers, and bacterial pneumonia.…”
Section: Health Benefits Of Quitting Smokingmentioning
confidence: 95%
See 1 more Smart Citation
“…28 Among HIV patients, quitting smoking also appears to convey substantial health benefits. For example, Lifson et al 26 reported that mortality among HIV patients in their sample was significantly higher throughout the follow-up period for current smokers than for former smokers. Current smokers were also more likely than former smokers to experience AIDS-related events (which include diseases meeting the revised CDC AIDS case definition as well as other conditions associated with HIV-related immunodeficiency, such as esophageal candidiasis), cardiovascular disease, non-AIDS cancers, and bacterial pneumonia.…”
Section: Health Benefits Of Quitting Smokingmentioning
confidence: 95%
“…Lifson et al 26 reported smoking data from a large (N = 5472) sample from the Strategies for Management of Antiretroviral Therapy clinical trial. Overall mortality was significantly higher for current than never-smokers.…”
Section: Smoking-related Morbidity and Mortality Among Plwhamentioning
confidence: 99%
“…4,22,[25][26][27][28][29][30][31] Compared with non-smokers, smokers have a two-fold or greater increased risk of MI 19 and CVD. 24,32 Although two studies have reported decreasing rates of smoking over time, in part suggesting that in an aging cohort, smoking rates are decreasing, 4,5 few data are available on actual rates of smoking as HIV-positive patients age. In the Swiss HIV Cohort Study, the prevalence of current smoking was lower among men older than 40 years compared with younger men (52.5% v. 64.3%, respectively), but not in women (53.4% v. 53.9%).…”
Section: Traditional Risk Factorsmentioning
confidence: 99%
“…Translational research has addressed a variety of medical conditions (e.g., cardiovascular disease, diabetes, and HIV/AIDS) and has been applied to medical, behavioral, and biobehavioral interventions (e.g., the Diabetes Prevention Program) [2]. Translation of behavioral interventions for people living with HIV/AIDS (PLWHAs) that addresses multiple risk behaviors is especially appropriate, as PLWHAs have been identified as being at increased risk of comorbid health conditions, such as cardiovascular and pulmonary diseases, depression, diabetes, and addiction [3,4]. In addition, psychiatric disorders have also been associated with decrements in essential health behaviors for PLWHAs (e.g., antiretroviral medication adherence [5][6][7][8][9] and medical appointment attendance [10,11]) and with poorer overall mental health and quality of life [12,13].…”
Section: Introductionmentioning
confidence: 99%